The Role of Biofilm Formation in Chronic Otitis Media, Pathogenesis, Clinical Impact, and Treatment Implications in ENT and Ophthalmology - Salman Ahmed Niaz Mangrio, Saira Bano, Allah Bux Mushtaq, Irshad Ali, Amir Zeb Khan, Abdul Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic Otitis Media (COM) is a persistent middle ear infection that significantly impacts patients' quality of life. The process of biofilm formation is essential for chronicity of the disease, antimicrobial resistance, and treatment failure. In this study, prevalence of biofilm producing bacterial isolates in COM patients, their antibiotic resistance pattern and clinical outcomes in Pakistan have been investigated. Methods: A cross-sectional study was done in ENT and Ophthalmology departement of tertiary care hospitals of Pakistan from January 2021 to September 2022. Bacterial identification, biofilm formation and antimicrobial resistance were analyzed in bacterial identification, biofilm formation and antimicrobial resistance in middle ear discharge samples from n=80 patients with COM. Congo Red Agar, Tube Method and Microtiter Plate Assay were used to detect biofilm. Kirby-Bauer disk diffusion method was used to assess antibiotic susceptibility. Follow up was for six months, and clinical outcomes were assessed. Results: The isolates formed biofilm in 72% of strains, the most frequent pathogens being Pseudomonas aeruginosa (40%) and Staphylococcus aureus (30%). Ciprofloxacin (85%), gentamicin (70%), ceftriaxone (60%), and meropenem (50%) resistance of biofilm-forming bacteria was significantly higher than the resistance of control bacteria (p < 0.05). Patients with biofilm present were more likely to have persistent infection (50%) and need surgery (17%) than patients without biofilm (14% and 8%, respectively, p = 0.0008). Conclusion: COM chronicity and treatment resistance are mediated in large part by biofilm formation. Optimization of treatment outcomes requires early detection, biofilm-targeted therapies, and improved antibiotic stewardship. Keywords: Chronic Otitis Media, Biofilm, Antimicrobial Resistance, Pseudomonas aeruginosa, Staphylococcus aureus, ENT Infections, Treatment Failure, Pakistan.